A holistic community-based architecture for measuring end-to-end QoS at data centres. (2015) - Zhanikeev, Marat
Data centres, the core of the rapidly growing world of cloud computing, do not support QoS. The main reason for this lack of support is the lack of QoS measurement data. Use of end-to-end active probing is not a feasible solution. Also, while data centres have direct access to incoming and outgoing traffic and can potentially analyse it, conventional traffic analysis tools cannot measure QoS. This paper proposes a new model of passive traffic monitoring which can facilitate end-to-end QoS measurement at data centres. The proposed architecture is holistic in nature and covers the full range of processing from packets to practical QoS metrics. To the knowledge of the authors, this is the first proposal of its kind in the related research community.